1999
DOI: 10.1016/s0002-9440(10)65217-0
|View full text |Cite
|
Sign up to set email alerts
|

Topical Estrogen Accelerates Cutaneous Wound Healing in Aged Humans Associated with an Altered Inflammatory Response

Abstract: The effects of intrinsic aging on the cutaneous wound healing process are profound , and the resulting acute and chronic wound morbidity imposes a substantial burden on health services. We have investigated the effects of topical estrogen on cutaneous wound healing in healthy elderly men and women , and related these effects to the inflammatory response and local elastase levels , an enzyme known to be up-regulated in impaired wound healing states. Eighteen health status-defined females (mean age , 74.4 years)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
310
2
5

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 368 publications
(328 citation statements)
references
References 23 publications
11
310
2
5
Order By: Relevance
“…27 Some authors reported that estradiol enhances the healing of tissue damaged by trauma. 28,29 It is known that estradiol promotes endothelial cell activities. 30,31 In our group, the duration of estrogen administration varied from 5 days to 16 weeks with a median duration of 5.5 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…27 Some authors reported that estradiol enhances the healing of tissue damaged by trauma. 28,29 It is known that estradiol promotes endothelial cell activities. 30,31 In our group, the duration of estrogen administration varied from 5 days to 16 weeks with a median duration of 5.5 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…46 In addition, oestrogenic effects on thermal injury have been well studied, for example, in the brain, where reduced inflammation and apoptosis are linked to lower levels of DAMPs. 68,69 Although oestrogen has been shown to promote acute wound healing in humans, 45 no data exist for its effect on infected cutaneous wounds. Here we show that oestrogen exerts beneficial effects on both epidermal and dermal aspects of cutaneous healing in a local LPS bacterial infection model.…”
Section: Oestrogen Restores Healing In Lps Model R Crompton Et Almentioning
confidence: 99%
“…Previous studies have shown a physiologically relevant role for oestrogen deficiency in delayed wound healing 44 and demonstrated beneficial effects of oestrogen supplementation in both mice and humans. [45][46][47] To our knowledge, the effects of oestrogen on bacterial infection of cutaneous wounds has yet to be studied. We thus assessed the effect of oestrogen treatment in our simple bacterial TLR4-stimulated wound model, showing for the first time that LPS-induced delayed healing can be reversed by the anti-inflammatory, pro-healing effects of oestrogen.…”
mentioning
confidence: 99%
“…Ashcroft et al [72] reported on dermal wound healing in aged males and females. Subjects had two upper inner arm punch biopsies and received either estrogen treatment or placebo for 24 hours.…”
Section: Macrophagesmentioning
confidence: 99%